2021
DOI: 10.3390/foods10020282
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Flours Obtained from Wasted Bread Crusts and Crumbs

Abstract: One third of the food produced in the world is wasted. Bread is one of the most wasted foods both during the distribution process and in households. To use these breads, it is necessary to get to know the properties of the flours that can be obtained from them. The purpose of this work is to know how the type of bread and its zone (crumb or crust) influence the characteristics of the flours obtained from the wasted bread. For this, flours made from the crumbs and crusts of eight different breads have been anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
1
21
1
Order By: Relevance
“…In fact, Fernández‐Peláez et al . (2021) have already observed that bread crust flours had higher a * and b * values and lower L * values than those obtained from crumbs. In terms of particle size, there is a tendency for L* values to increase and for a decrease in a * and b * as the particle size decreases.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In fact, Fernández‐Peláez et al . (2021) have already observed that bread crust flours had higher a * and b * values and lower L * values than those obtained from crumbs. In terms of particle size, there is a tendency for L* values to increase and for a decrease in a * and b * as the particle size decreases.…”
Section: Resultsmentioning
confidence: 87%
“…Fernández‐Peláez et al . (2021) have attributed these differences to the presence of such ingredients as oil and to the lower content of starch and protein responsible for water hydration. It is possible to think that in bread crusts, the gelatinised starch content is lower resulting in a lower water absorption capacity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Demirci et al [ 15 ] a high optimal LIQ temperature could be explained because this temperature makes it easier for enzymes to attack starch granules. However, we must take into consideration that we are working with bread flour when the starch is pre-gelatinized (almost) completely [ 27 , 28 , 29 ]. Moreover, this temperature may be due to the chosen enzyme, whose recommended range of action is between 80–85 °C (data provided by Novozyme).…”
Section: Resultsmentioning
confidence: 99%